Optimized MBR for greywater reuse systems in hotel facilities. (15th May 2017) - Atanasova, Natasa; Dalmau, Montserrat; Comas, Joaquim; Poch, Manel; Rodriguez-Roda, Ignasi; Buttiglieri, Gianluigi
Abstract: Greywater is an important alternative water source, particularly in semi-arid, touristic areas, where the biggest water demand is usually in the dry period. By using this source wisely, tourist facilities can substantially reduce the pressure to scarce water resources. In densely urbanized touristic areas, where space has high value, compact solutions such as MBR based greywater reuse systems appear very appropriate. This research focuses on technical and economical evaluation of such solution by implementing a pilot MBR to a hotel with separated grey water. The pilot was operated for 6 months, with thorough characterisation of the GW performed, its operation was monitored and its energy consumption was optimized by applying a control system for the air scour. Based on the pilot operation a design and economic model was set to estimate the feasibility (CAPEX, OPEX, payback period of investment) of appropriate scales of MBR based GW systems, including separation of GW, MBR technology, clean water storage and disinfection. The model takes into account water and energy prices in Spain and a planning period of 20 years. The results demonstrated an excellent performance in terms of effluent quality, while the energy demand for air-scour was reduced by up to 35.2%, compared to the manufacturer recommendations. Economical evaluation of the entire MBR based GW reuse system shows its feasibility for sizes already at 5 m 3 /day (60 PE). The payback period of the investment for hotels like the demonstration hotel, treating 30 m 3 /day is 3 years. Graphical abstract: Highlights: MBR based GW reuse systems are feasible alternative for hotels. GW MBR can reduce energy consumption for the air scour by 35.2% on average. Hotels that treat 30 m 3 /day (300 rooms) achieve payback periods of 3 years. These systems can reduce WW generation in Lloret de Mar (Spain) by 30%.